Fibroblast Growth Factor and Mineral Metabolism Parameters among Prevalent Kidney Transplant Patients - Madhumathi Rao; Priyanka Jain; Temitope Ojo; Gautam Surya; Vaidyanathapuram Balakrishnan (International Journal of Nephrology)
Background. Chronic kidney disease (CKD) related mineral bone disorders persist after kidney transplantation, but little is known about the relationship between fibroblast growth factor-23 (FGF-23) and mineral metabolism in prevalent post-transplant patients. Objectives. To examine mineral metabolism parameters and their relationship to FGF-23 and parathyroid hormone (PTH) in prevalent kidney transplant patients. Methods. Cross-sectional study of 106 kidney transplant patients enrolled November 2005–October 2009 at Tufts Medical Center (TMC), Boston. Results. The prevalence of hypophosphatemia was 34%, hypercalcemia 3%, and elevated PTH levels 66%, at a median (25th–75th percentile) duration of 12.8 (7.5–30.9) months post-transplant. Males had significantly higher levels of PTH (P=0.04) and lower levels of serum phosphate (P=0.002). Serum PTH levels did not relate to eGFR, corrected calcium levels or serum phosphate. FGF-23 levels were above the reference limits in 7% of patients; higher levels were associated with higher serum phosphate and PTH levels after adjustment for transplant kidney function. Conclusion. FGF-23 is an important driver of mineral metabolism in prevalent transplant patients. Its modulatory role in mineral metabolism homeostasis may be heightened as feedback suppression of PTH is disturbed. Its role in long term cardiovascular and graft outcomes needs further study.